Therapeutic insulin and hepatic glucose-6-phosphatase activity in preterm infants. Issue 3 (1st May 2000) - Burchell, A; McGeechan, A; Hume, R
Abstract : BACKGROUND: Hepatic glucose-6-phosphatase activity is low at birth, and in term infants rises rapidly to adult levels. In contrast, in most preterm infants, it remains low postnatally making them vulnerable to repeated hypoglycaemic episodes, resultant cerebral damage, or risk of sudden and unexpected death. AIMS: To investigate the clinical features of preterm infants with low glucose-6-phosphatase enzyme activity to determine the influencing factors. METHODS: Clinical data from 36 preterm infants were correlated by stepwise multiple regression analysis with Vmax of hepatic glucose-6-phosphatase as the dependent variable. RESULTS: The most significant correlation was with the administration of insulin (units/kg/h postnatal life) with lesser effects of respiratory distress syndrome and dopamine administration. The Vmax changes reflected changes in the level of expression of the glucose-6-phosphatase protein. CONCLUSION: In a variety of animal models, hepatic glucose-6-phosphatase levels have been shown to decrease in response to insulin, which also decreases transcription of the glucose-6-phosphatase gene. The association of insulin administration with high levels of hepatic glucose-6-phosphatase activity and protein expression was therefore most unexpected. Results from model systems, or adults, must be extrapolated to the metabolism of preterm infants with caution.